Sociolinguistics and Business Talk A Role-Playing Approach - Jung, Yeonkwon (Singapore : Springer Nature Singapore : Imprint: Palgrave Pivot, 2022)
This book delivers essential skills in "spoken" professional communications, presenting theoretical and applied frameworks for business talk using English as a lingua franca. Adopting a role-playing approach mimicking various professional settings, it assesses the strength of the well-reasoned argument, the logical links that convince the audience of the coherence of the speaker's argument and the necessary linguistics competencies. This book centers on a variety of situations that commonly take place in business organizations (such as relational talk; call center talk; job application talk) and addresses key skills such as conflict resolution and collaborative problem solving through communication, which are key for both students and practitioners. In addition it analyses spoken business discourse data with the four main sources of communicative competence: grammatical competence, discourse competence, sociolinguistic competence and strategic competence in order to highlight how they are used in business speaking practices. Yeonkwon Jung is Associate Professor of Communication at Kansai Gaidai University, where he is a coordinator of the MA program in English Communication. Prior to joining Kansai Gaidai University, he held numerous teaching and research appointments, including University of Michigan at Ann Arbor, Chuo University, and Korea University. He holds a PhD from the University of Edinburgh and an MA from University of Hawaii. His major research interests include the various genres of business communication, the role of English as the business lingua franca, and corporate communication in international contexts. He has published articles in a wide range of international journals and books, such as "Genre variation in business letter writing", "Asian business discourse(s)" (both from Peter Lang), "Professional Communication" (Hong Kong University Press), and "The Handbook of Business Discourse" (Edinburgh University Press).
1 Introduction -- 2 Rapport talk -- 3 Call center talk -- 4 Business meeting talk -- 5 Sales talk -- 6 PR talk -- 7 Job application talk -- 8 Concluding remarks.
Keywords: Sociolinguistics; Linguistics; Marketing; Career education; Sociolinguistics; Linguistics; Marketing; Career Skills